MODERASI BIAYA BERALIH PADA PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN (Studi pada PTS X) - Hermansyah Andi Wibowo (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: This study aims to examine the moderating role of switching cost on two effects, which are: the effect of service quality on customer satisfaction and service quality effect on customer loyalty. In addition, this study also examines the effect of service quality, switching cost and customer satisfaction, on customer loyalty. Finally, the effect of service quality on customer satisfaction is also tested. The analysis tool used is SEM with LISREL 8.80 software. In order to implement the results, it was conducted the correlation analysis between the dimensions of the independent variables with dimensions on the dependent variable. As a result, the switching cost is not provenas a moderator variable. Service quality has positive and significant effects on customer satisfaction and customer loyalty. Switching cost is proven positively and significantly effects customer loyalty. It was proven that customer satisfaction did not effects customer loyalty. Dimensions which dominant correlated are: the dimension of empathy with the core service dimension, dimension of empathy with dimension of loyalty attitude; and dimension of relational cost with behavioral loyalty dimension.Keywords: customer loyalty, service quality, customer satisfaction, switching cost, moderation, dimensions correlation.